(untitled) (Stato, Chiese e pluralismo confessionale, 2022)
SOMMARIO: 1. Osservazioni introduttive circa la disciplina degli enti religiosi alla luce del codice del Terzo settore - 2. Cenni al binomio sport-religione - 3. Il caso del Centro Sportivo Italiano (CSI) - 4. Brevi considerazioni conclusive alla luce del documento “Dare il meglio di sé”. Religious inspired sports bodies. The ‘Centro Sportivo Italiano’ case. ABSTRACT: After an overview and highlighting of the most recent changes introduced to the Code of the Third Sector and of the wide range of interplay and frictions between religion and sport, from a legal perspective, the contribution focuses on the religious inspired sports bodies. Among these, the paper discusses the case of the Centro Sportivo Italiano and examines its statutes and association pact that outline the Catholic religious orientation. The essay ends by considering the 2018 document “Giving the best of yourself” of the Dicastery for the Laity, Family and Life, which can be described as the first real Catholic manifesto on the Catholic perspective on sport and human person.